Off Grid Solar System Without Using Battery Storage (Hydro Part) - Elias, Muhammad Danial; Abd Razak, Mohd Fadly (Progress in Engineering Application and Technology, 2024)
Battery storage for renewable energy like solar and water has high costs and environmental impacts. This project explores an alternative by combining solar and small-scale hydroelectric power. Photovoltaic panels generate electricity from sunlight, while a designed hydroelectric system uses flowing water for power generation. This study focuses on the hydroelectric system, aiming to show its efficiency and practicality as an alternative to battery storage. By creating a prototype, we demonstrate that solar and hydroelectric power together can provide a sustainable and cost-effective energy solution for homes, addressing both financial and environmental concerns.